Humor is a Universal Phenomenon - Ziyayeva Kamola Ziyaiddinovna (Genius Publishing Group, 2022)
The paper describes humor as a difficult subject for modern linguistics. In addition, it analyzes the peculiarities and incomprehension of jokes in English. The article contrasts Uzbek and English cultures.
Keywords: humor; universal phenomenon; the cultural aspect; English jokes